KETIDAKSTABILAN INFLASI VS GEJOLAK SAHAM: DINAMIKA ICBP DI PANDEMI COVID-19 TAHUN 2020 - 2023 - Naufal Khadaf (Jurnal Ekonomi, Bisnis dan Pendidikan, 2024)
AbstractThis study analyzes the relationship between inflation volatility and stock pricevolatility of PT Indofood CBP Sukses Makmur Tbk (ICBP) during the COVID-19pandemic (2020-2023). ICBP, a major player in Indonesia's consumer goodssector, faced significant economic fluctuations due to global instability duringthe pandemic. Using secondary data from monthly inflation rates and ICBPstock prices, the research employs the Jarque-Bera normality test for datavalidation and the Pearson correlation test to examine the relationshipbetween the two variables. The results show a significant negative correlationof -0.467051 (p < 0.05) between inflation volatility and stock price volatility. Thissuggests that higher inflation volatility is associated with lower stock pricevolatility, which can be explained by theories like the Fisher Effect and theDiscounted Cash Flow (DCF) model, where inflation reduces purchasingpower and increases discount rates. Additionally, the study highlights thesensitivity of the consumer goods sector to macroeconomic factors such asinflation. This research offers insights for investors and policymakers,emphasizing the role of inflation in influencing stock market dynamics. Itunderscores the importance of portfolio diversification to mitigate risks arisingfrom global economic uncertainties and provides policy recommendations forfostering economic and financial stability.